Social media power for protest in Indonesia: The Yogyakarta’s #gejayanmemanggil case study - Fuadi, Ariza (Jurnal Studi Komunikasi, 2020)
Hashtag #GejayanMemanggil (Gejayan is Calling) became a trending topic on social media one day before the protest against several problematic laws, and the bills that were going to be passed. At that time, activists had successfully circulated the issues to the public through social media. As a result, at least 5000 protesters had joined in the protest in Yogyakarta. This phenomenon showed activeness of Indonesia’s civil society in the movement by involving digital media technologies. The author argued that social media allows the citizens, either communal or individual, to disseminate the issue and encourage others to join the protest in such short notice. This article aims to describe the role of social media and the impact of mobilisation through social media through the hashtag #GejayanMemanggil in the Yogyakarta movement. The qualitative method was employed to examine the phenomenon of the protests and to describe the role of social media. The data in this study was taken from online news, the official account of the movement, and blog posts. The results indicated that social media has the potential to trigger Indonesians to express their willingness and participate in activism.